Synthesis of functionalized γ-lactams by a lewis acid catalyzed ketene formation/cyclization/claisen rearrangement sequence of 5, 5-disubstituted Meldrum's acid. (8th June 2022) - Lin, Xiao-Wan; Han, Mei; Shen, Mei-Hua; Zhu, Chi-Fan; Xu, Hua-Dong
Graphical abstract: Abstract: A series of γ-lactams were synthesized by intramolecular aza-claisen rearrangement of ketenes using Meldrum's acid as ketene precursor. Derivatives of Meldrum's acid with tertiary ammonia structure were used as raw material, and the reaction was catalyzed by Lewis acid at high-temperature conditions under microwave. Ketene formation by losing acetone and CO2, cyclization and claisen rearrangement occurred in sequence to form the γ-lactams.